Warisan Leluhur dalam Tetesan Gula: Etnografi Ekonomi Gula Aren di Dusun Balibak, Bawean - Faiz, R. Moh. Edi; Widodo, Wahono; Gunansyah, Ganes (Innovations in Multidisciplinary Education Journal, 2025)
This research aims to reintroduce local cultural heritage in the form of palm sugar production to the younger generation of Bawean people, especially in Balibak Hamlet. Palm sugar is not only a part of the community's daily life, but also represents hereditary knowledge that is rich in cultural and economic values. Through an ethnographic approach, this research explores in depth the process of making palm sugar, starting from tapping the sap of the palm tree, traditional processing using firewood, to the molding and packaging process using kelaras (dried banana leaves). Data was collected through direct observation, in-depth interviews with sugar makers, and documentation of their daily activities. The results showed that palm sugar making requires not only technical skills, but also patience and thoroughness that are passed down orally from generation to generation. In addition, traditionally produced palm sugar has a more natural and low-glycemic nutritional content, making it a healthier alternative to granulated sugar. Other findings show that palm sugar products have promising economic potential, both in the local market and as a regional specialty product that deserves to be promoted more widely. The research recommends the integration of this local knowledge into contextualized learning for Bawean children and youth, so that this cultural heritage is preserved and provides economic benefits in Bawean.